2017
DOI: 10.1542/peds.2016-3518
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Label: Steering the Focus Toward Safe and Effective Prescribing

Abstract: Each year, hundreds of millions of prescription medications are dispensed to pediatric patients. 1 A significant proportion of prescriptions are used in an off-label manner, outside the specifications approved by the US Food and Drug Administration (FDA), rendering off-label prescribing a "public health issue for infants, children and adolescents, " as described by the Committee on Drugs for the American Academy of Pediatrics. 2 The committee also explicitly states that off-label use "does not imply an imprope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A total of 5109 publication records were screened, 31 of which were included in the analysis (Figure 1). Of these, 21 (68% of total) publications refer to 20 unique guidances providing general considerations, frameworks, and recommendations to guide decision‐making for off‐label medicines use 8,14–17,22–37 . Ten papers (32%) provided off‐label use recommendations for specific medicines or therapeutic categories but also described the types of evidence, expertise, and processes used in developing recommendations and thus were included 38–47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 5109 publication records were screened, 31 of which were included in the analysis (Figure 1). Of these, 21 (68% of total) publications refer to 20 unique guidances providing general considerations, frameworks, and recommendations to guide decision‐making for off‐label medicines use 8,14–17,22–37 . Ten papers (32%) provided off‐label use recommendations for specific medicines or therapeutic categories but also described the types of evidence, expertise, and processes used in developing recommendations and thus were included 38–47 …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 21 (68% of total) publications refer to 20 unique guidances providing general considerations, frameworks, and recommendations to guide decision-making for offlabel medicines use. 8,[14][15][16][17][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Ten papers (32%) provided off-label use recommendations for specific medicines or therapeutic categories but also described the types of evidence, expertise, and processes used in developing recommendations and thus were included. [38][39][40][41][42][43][44][45][46][47] 3.1.2 | Thematic concepts of general guidances for off-label medicine use…”
Section: Identification Of Relevant Papersmentioning
confidence: 99%
“…Drugs used in precision medicine, and the biomarkers on the basis of which these drugs are prescribed, are oftentimes relatively novel. In addition, in precision medicine, off-label prescription (i.e., prescription for indications not authorized by regulatory agencies), is even more common than in many other fields of medicine [36,37]. As a result, patients who are prescribed precision medicine interventions face different, and comparatively more unknown, risks than patients in the stereotypical contexts for which the LHS concept has originally been developed.…”
Section: Changing the Treatments That Are Prescribed On The Basis Of These Testsmentioning
confidence: 99%
“…Studies have found that 42%–73% of drug prescriptions in patients under 18 years were off-label, with the highest frequencies reported in neonates ( Cuzzolin and Agostino, 2016 ; Hoon et al, 2019 ; Yackey et al, 2019 ; van der Zanden et al, 2022 ). However, off-label use does not mean off-evidence nor does it imply improper or contradicted use ( COMMITTEE ON DRUGSNeville et al, 2014 ; Czaja et al, 2017 ). Highly prescribed drugs off-label may have strong evidence for safe and effective use, yet a formal application for regulatory authorization may not be sought ( Czaja et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, off-label use does not mean off-evidence nor does it imply improper or contradicted use ( COMMITTEE ON DRUGSNeville et al, 2014 ; Czaja et al, 2017 ). Highly prescribed drugs off-label may have strong evidence for safe and effective use, yet a formal application for regulatory authorization may not be sought ( Czaja et al, 2017 ). In a recent study of the Dutch Pediatric Formulary, 42% of prescribed drug records were off-label, of which only 14% were supported by high-quality evidence and 37% by expert opinion ( van der Zanden et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%